2015
DOI: 10.4236/ojog.2015.511086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Postpartum Depression in Yaounde, Cameroon

Abstract: Introduction: Postpartum Depression is one of the commonest complications of the postpartum period. In Cameroon, little is known about this condition. Our objective was to determine the prevalence and identify the risk factors for postpartum depression. Methodology: The study was carried out at the Yaoundé Gyneco-Obstetric and Pediatric Hospital, from November 4th 2013 to April 4th 2014. All the women between the 4th and 6th week after birth who gave their consent were included. A pretested questionnaire inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
31
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 14 publications
18
31
5
Order By: Relevance
“…This finding was in contrast to a study by Adama et al, 2015 which confirmed that the same factor not considered as co-factor for PPD due to a non-significant relationship between type of childbirth and PPD. 26 Our study confirmed the idea that the level of education is a contributing factor for postpartum depression taking into consideration that the PPD prevalence is highest in highly educated women that might be related to their life style and involvement in different works and jobs. Our finding contradicts Mohammed et al, 2014 10 and Zagade & Deshpande, 2013 24 studies in which they observed that the prevalence of PPD among high school educated mothers was more than other educational levels.…”
Section: Discussionsupporting
confidence: 74%
“…This finding was in contrast to a study by Adama et al, 2015 which confirmed that the same factor not considered as co-factor for PPD due to a non-significant relationship between type of childbirth and PPD. 26 Our study confirmed the idea that the level of education is a contributing factor for postpartum depression taking into consideration that the PPD prevalence is highest in highly educated women that might be related to their life style and involvement in different works and jobs. Our finding contradicts Mohammed et al, 2014 10 and Zagade & Deshpande, 2013 24 studies in which they observed that the prevalence of PPD among high school educated mothers was more than other educational levels.…”
Section: Discussionsupporting
confidence: 74%
“…In the social support dimension, respondents who had poor social support were higher in odds to be depressed than those who had strong social support. The association in estimation was in line with studies done in Malaysian and Pakistan (24), Cameron; Yaoundé (28) and Hiwot Fana specialized University Hospital in Ethiopia (11). In fact, having poor social support is one of risk of mental health problems.…”
Section: Factors Associated With Postpartum Depressionsupporting
confidence: 89%
“…The association between not attempting breastfeeding and risk of PPD is controversy, Pope CJ et al [17] concluded that breastfeeding status alone may not be a significant risk factor for PPD. However, this study examined the breastfeeding difficulties and found positive association with risk of PPD, similar to another study [10]. It is therefore, suggested that infant's illnesses, prematurity, maternal perception of infant health status together with lack of support, are significant contributors to PPD.…”
Section: Discussionsupporting
confidence: 77%
“…Fairbrother N, in recent study reported prevalence ranges between 11 -21% [9]. Another study from Africa observed higher incidence as 23.4% [10]. However, there is variability in the prevalence of PPD across different geographical locations and population groups.…”
Section: Discussionmentioning
confidence: 94%